Catalytic application of sulfonic acid‐functionalized titana‐coated magnetic nanoparticles for the preparation of 1, 8‐dioxodecahydroacridines and 2, 4, 6‐triarylpyridines via anomeric‐based oxidation. (24th October 2017) - Zolfigol, Mohammad Ali; Karimi, Fatemeh; Yarie, Meysam; Torabi, Morteza
Abstract : We have developed green, efficient and powerful protocols for the preparation of 2, 4, 6‐triarylpyridines and 1, 8‐dioxodecahydroacridines in the presence of Fe3 O4 @TiO2 @O2 PO2 (CH2 )2 NHSO3 H as a sulfonic acid‐functionalized titana‐coated magnetic nanoparticle catalyst under mild and solvent‐free reaction conditions. These protocols furnished the desired products in short reaction times with good to high yields (20–40 min and 80–86% in the case of 2, 4, 6‐triarylpyridines; 15–90 min and 80–93% in the case of 1, 8‐dioxodecahydroacridines). The final step of the mechanistic route in the synthesis of 2, 4, 6‐triarylpyridines proceeds via an anomeric‐based oxidation. Also, the nanomagnetic core–shell catalyst can be recycled and reused in both cases of the scrutinized one‐pot multicomponent reactions with high turnover number and turnover frequency. Abstract : Syntheses of 2, 4, 6‐triarylpyridines and 1, 8‐dioxodecahydroacridines were carried out in the presence of a catalytic amount of Fe3 O4 @TiO2 @O2 PO2 (CH2 )2 NHSO3 H. The Triarylpyridines were prepared via an anomeric‐based oxidation route.